The impact of video-based presentations on BPED students' learning performance - Culajara , Carla Jobelle (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2022)
The main objective of this study was to determine and evaluate the effectiveness of video-based presentations in providing physical education instructions. This quantitative research used a quasi-experimental which was participated by 46 students taking Bachelor of Physical Education (BPED) in one of the tertiary schools in the Philippines which were assigned into two intact groups: experimental and control groups. The study used ANOVA to find a significant difference at 0.05 level in time variables within the group with a p-value of <0.001. It means that there are changes in the pre-test and post-test scores. As a result, it makes a substantial effort to support in the deepening and continual attainment of the learning competencies expected of future Physical educators through video-based presentations. Based on the findings of the study, as the driving factor for attaining the aforementioned goals, teachers must have an interest in learning and grow through professional growth, and self-improvement, as well as the academic performance of the students through the development and improved learning, it means that there are changes in the pre and post scores. This study will be the baseline of information for future researchers who will do comprehensive research on video-based presentations and the integration of technology in the delivery of Physical Education teachings.